Effect of health education on self-care behavior in patients with type 2 diabetes mellitus - Syaharuddin, Syaharuddin; Suprapto, Suprapto; Arda, Darmi; Menga, Maria Kurni; Martinez, Rudolf Cymorr Kirby (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder requiring continuous self-care to prevent complications. Health education plays a crucial role in enhancing patients’ understanding, attitudes, and skills for effective self-management. This study aimed to investigate the impact of health education on self-care behaviors among patients with Type 2 Diabetes Mellitus. Methods: This quasi-experimental study employed a pretest–posttest design with a control group. The study involved 60 patients with type 2 diabetes mellitus (T2DM) selected using purposive sampling from a public health center. The intervention group received structured health education sessions covering diet management, physical activity, medication adherence, and blood glucose monitoring for a period of four weeks, while the control group received standard care. Data were collected using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Statistical analysis was conducted using paired and independent t-tests with a significance level of p < 0.05. Results: The findings showed a significant increase in self-care behavior scores in the intervention group after receiving health education (p < 0.001), while no significant change was observed in the control group (p > 0.05). The mean difference between the two groups indicated that health education had a positive effect on self-care behavior among patients with T2DM. Conclusion: Health education has a significant impact on improving self-care behaviors among patients with Type 2 Diabetes Mellitus. Structured and continuous education increases patients’ awareness, adherence, and ability to manage diet, exercise, medication, and blood glucose monitoring effectively. Healthcare providers should integrate regular health education programs into diabetes management to enhance patients’ self-care skills and prevent complications. Further research with larger samples and longer follow-up is recommended to evaluate the long-term impact of such interventions.